Pengaruh Penerapan Model Teams Games Tournament TGT Dalam Meningkatkan Hasil Belajar PAI di Fase F SMAN 2 Bayang Kecamatan Bayang Kabupaten Pesisir Selatan - Vira Hapena Putri; Ulva Rahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The results obtained in the descriptive analysis illustrate the effect of applying the tournament model of TGT team games. Based on the frequency distribution table 4.9, students experimental class of F1 phase were of high ability, i.e. 13 students who received scores in the ranges 0f 95-100. Meanwhile, one low-ability student received an average grade of 75-80. And moderate student is 12 and average marks are 90-95. At the same time in the control class of phase F2. Based on the frequency distribution table given in point 4.10, students have an average ability, i.e. 9 students at the average level of 80-85. At the same time there were 4 students with weak skills who received an average grade of 70-75. And there are 5 highly qualified students who scored average 95-100. As a result of the analysis, descriptive testing of the hypothesis, descriptive analysis received a sig value of 0.000 and it is less than 0.05 the show it more significant learning using the in learning Islamic religious education. In addition, the decision can also be seen in the table tcount >. To find the table values, the researcher used a t-distribution table 0.05, so the T-value of the experimental class was 86.144 > 0.05 and the T-value of the control class (F2) was 57.608 > 0.05 From the results of both points, ie. 86 144 > 57 608. So we can conclude that ho is rejected and Ha is accepted. Based on these calculations, the application of Team Games Tournament (TGT) learning model to PAI learning outcomes in Phase F of SMAN 2 Bayang, bayang piiri, pesiri selatan can be liked.